pH-Triggered Assembly of Natural Melanin Nanoparticles for Enhanced PET Imaging - Liu, Qingyao; Fang, Hanyi; Gai, Yongkang; Lan, Xiaoli (Frontiers in Chemistry, 2020)
Natural melanin nanoplatforms have attracted attention in molecular imaging. Natural melanin can be prepared into ultra-small-sized nanoparticles, which penetrate tumor sites deeply, but unfortunately, the particles continue to backflow into the blood or are cleared into the surrounding tissues, leading to loss of retention within tumors. Here, we report a pH-triggered approach to aggregate natural melanin nanoparticles by introducing a hydrolysis-susceptible citraconic amide on the surface. Triggered by pH values lower than 7.0, such as those in tumor tissues that are often rendered acidic by hypoxia, the citraconic amide moiety tended to hydrolyze abruptly, resulting in both positive and negative surface charges. The electrostatic attractions between nanoparticles drove nanoparticle aggregation, which increased accumulation in the tumor site because backflow was blocked by the increased size. Melanin nanoparticles have the natural ability to bind metal ions, which can be labeled with isotopes for nuclear medicine imaging. When the melanin nanoparticles were labeled by 68Ga, we observed that the pH-induced physical aggregation in tumor sites resulted in enhanced PET imaging. The pH-triggered assembly of natural melanin nanoparticles could be a practical strategy for efficient tumor target imaging.